Crisis and Visual Critique. Issue 1 (12th May 2016) - Pinney, Christopher
Abstract: Perspectives from this special issue on Greece are folded into a discussion of the current post‐Foucauldian and "neo‐Benjaminian" moment of contemporary photographic theory and visual culture. Bourdieu's ethnography of photography is contrasted with his own photographic practice and considered in light of Azoulay's Civil Contract of Photography. The return to the "event" of photography and an understanding of its contingency reawakens its revolutionary potential. [visual culture, crisis, Pierre Bourdieu, Ariella Azoulay]